Penerapan Model Pembelajaran Stad Untuk Meningkatkan Hasil Belajar Bangun Datar Kelas IV SDN 193/V Dusun Mudo - Eka Sastrawati; Desri Guspita (Jurnal Ilmiah Wahana Pendidikan, 2022)
In the application of the STAD learning model, it consists of five steps, namely class presentation, group learning activities, individual tests, determining individual score increases, and group rewards. This study aims to improve the learning outcomes of flat shapes for fourth grade students of SDN 193/V Dusun Mudo in the even semester of 2020/2021. The approach used in this research is a qualitative approach and the type of research is classroom action research. The results of research conducted on 30 students are as follows: in cycle 1 of meeting 1, the learning outcomes of students are 6.8. Actions in the first cycle of the second meeting obtained an average learning outcome of 7.5. In general, the implementation of the first cycle of the second meeting compared to the first cycle of the first meeting was better. The action in the second cycle is to prove that the learning outcomes obtained by students continue to increase and the learning outcomes obtained are 8.3. From the results of the study, it is evident that the use of the STAD model can improve student learning outcomes.